The State-of-the-Art Brief Review on Piezoelectric Energy Harvesting from Flow-Induced Vibration - Hongjun Zhu; Tao Tang; Huohai Yang; Junlei Wang; Jinze Song; Geng Peng (Shock and Vibration)
Flow-induced vibration (FIV) is concerned in a broad range of engineering applications due to its resultant fatigue damage to structures. Nevertheless, such fluid-structure coupling process continuously extracts the kinetic energy from ambient fluid flow, presenting the conversion potential from the mechanical energy to electricity. As the air and water flows are widely encountered in nature, piezoelectric energy harvesters show the advantages in small-scale utilization and self-powered instruments. This paper briefly reviewed the way of energy collection by piezoelectric energy harvesters and the various measures proposed in the literature, which enhance the structural vibration response and hence improve the energy harvesting efficiency. Methods such as irregularity and alteration of cross-section of bluff body, utilization of wake flow and interference, modification and rearrangement of cantilever beams, and introduction of magnetic force are discussed. Finally, some open questions and suggestions are proposed for the future investigation of such renewable energy harvesting mode.